2020
DOI: 10.1088/1755-1315/411/1/012059
|View full text |Cite
|
Sign up to set email alerts
|

Farming Bot: Precision Agriculture System in Limited Land Based On Computer Numerical Control (CNC)

Abstract: Indonesia is a vast country both sea and land, but as population development and growth continues to increase, the land that is usually used for agricultural land is now changing into residential land. This narrowing land is the biggest challenge that must be faced today. Basically, farming activities require a knowledge base that is land use, seeds/seedlings, cultivation, processing, to marketing. However, cultivation on land is limited by several methods of land use such as the use of roof gardens need to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
0
6
0
7
Order By: Relevance
“…In Figure 2, it can be seen that the linear speed of each wheel is the same, while the angular velocity of wheel A and wheel B is different, because it is influenced by the radius of each wheel. The relationship of the tangent wheels is two wheels that are glued together so that they are tangent and have opposite rotational directions [19] can be seen in the following figure: From Figure 3 it can be concluded that the linear speed of wheel A and wheel B are the same, while the angular velocity of wheel A and wheel B are different, because it is influenced by the difference in the radius of each wheel. From experiments on the three related wheel motions students can find out the justification of the theory learned in class, and can compare the differences in angular velocity, linear velocity, and the influence of the radius on each wheel.…”
Section: Figure 2 Wheel Motion With Ropementioning
confidence: 99%
“…In Figure 2, it can be seen that the linear speed of each wheel is the same, while the angular velocity of wheel A and wheel B is different, because it is influenced by the radius of each wheel. The relationship of the tangent wheels is two wheels that are glued together so that they are tangent and have opposite rotational directions [19] can be seen in the following figure: From Figure 3 it can be concluded that the linear speed of wheel A and wheel B are the same, while the angular velocity of wheel A and wheel B are different, because it is influenced by the difference in the radius of each wheel. From experiments on the three related wheel motions students can find out the justification of the theory learned in class, and can compare the differences in angular velocity, linear velocity, and the influence of the radius on each wheel.…”
Section: Figure 2 Wheel Motion With Ropementioning
confidence: 99%
“…Hal tersebut dapat dilihat dari tanda pada tanaman berupa daun dan batang yang berwarna kuning sehingga menyebabkan daya tawar sayuran rendah, sehingga mendapatkan harga jual yang jauh dipasaran (Tando, 2019). Adanya berbagai permasalahan ini, menuntut aplikasi teknologi yang berbasiskan Contactless technology (Kautsar et al, 2020;Wijaya et al, 2020) pada Greenhouse Rumahku Hidroponik, melalui kegiatan program pemberdayaan masyarakat UKM Indonesia bangkit terutama dalam menangapi situasi saat ini ketika musibah penyakit Covid-19 masih melanda di Tanah Air. Berdasarkan Fairuz et al, (2020), Contactless technology dapat mengatasi permasalahn di era pandemic covid.…”
Section: Pendahuluanunclassified
“…Teknologi computer numerical control (CNC) telah banyak diterapkan untuk menunjang pertanian. Teknik CNC diimplementasikan untuk menanam sayuran pada area yang terbatas [9]- [11]. Sistem tersebut dapat dikontrol secara jarak jauh untuk menanam sayuran pada media tanam tanah.…”
Section: Kata Kunciunclassified